Web-Based Information System Of Drug Sales At Zamili Jaya Pharmacy - Niscaya Zamili; R L Harmady Tamba (Cattleya Darmaya Fortuna, 2022)
The development of information and communication technology has benefits and has a major impact on various aspects of human life. The development of this technology is not only in education, but also in sales, for example in the sale of medicines in pharmacies. Pharmacy is a business activity in the health sector that requires a data processing system to simplify and speed up operations. Zamili Jaya Pharmacy which is located at Jl. Veteran Psr 7 Helvetia is a pharmacy that still uses the manual method in its sales process. Manual sales process is believed to reduce salesperson service performance. Therefore, a web-based drug sales information system was launched that could support and facilitate drug sales. This study aims to find out or determine whether the sales information system implemented at Zamili Jaya Pharmacy is running well and supporting the sales process. The method used to analyze this data is observational. The structure of this system with programming languages ​​PHP, HTML, Bootstrap and MySQL database. The end result of the system built is the drug management information system for the Zamili Jaya Pharmacy.